Call of the American wild : a tenderfoot's escape to Alaska - Grieve, Guy, 1973- (Skyhorse Pub., 2012)
A man, an axe, and a dog named Fuzzy ... let the adventure begin. Trapped in a job he hated and up to his neck in debt, Grieve's life was going nowhere. When his dream of escaping it all to live in remote Alaska suddenly came true, he was miles from the nearest human being and armed with only the most basic equipment. Grieve began carving a life for himself through fishing, hunting-- and diligently avoiding bears.